Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Others" - - (Hygeia Press di Corridori Marinella, 2018)
Selected Abstracts of the 8th International Congress of UENPS; Bucharest (Romania); October 3rd-5th 2018; Session "Others" ABS 1. CRYING WOLF: ALARM FATIGUE AND RESPONSE TIMES FOR VASOACTIVE INFUSIONS • J. Waterson, S. Garcia, C. Vollmer, S. Rolt ABS 2. TYPES OF CONGENITAL MALFORMATIONS AT PRETERM AND TERM NEWBORNS • G. Noditi, D. Iacob, I. Enatescu, N. Ionita, M. Pantea, E.R. Iacob ABS 3. LABORATORY AND GAS-ANALYSER CONCORDANCE IN THE NEONATAL POPULATION • I. Ahmed, N. Subbaraya, M. Cawsey ABS 4. THE CONTRIBUTION OF GENETIC DETERMINANTS TO ADVERSE TREATMENT OUTCOMES IN PREMATURELY BORN INFANTS WITH SEVERE INTRAVENTRICULAR HEMORRHAGES • T. Znamenska, O. Kovalova, V. Pokhylko, N. Artyomova, S. Tsvirenko, Y. Cherniavska, O. Vorobiova